2020
DOI: 10.1038/s41584-020-0427-z
|View full text |Cite
|
Sign up to set email alerts
|

Combating physical inactivity during the COVID-19 pandemic

Abstract: Physical inactivity is common during periods of self-isolation, but for patients with rheumatic diseases, there are crucial benefits to be gained from maintaining an active lifestyle throughout the COVID-19 pandemic. Patients should be provided with support to maintain physical activity and avoid prolonged periods of time spent sitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 8 publications
3
127
0
13
Order By: Relevance
“…As a timely example amidst the COVID-19 pandemic (Pinto et al, 2020), SIT-WB requires no additional equipment and can be easily performed alone indoors or outdoors. Give that another rising ACSM fitness trend (thirteenth position) is outdoor activities, it appears that there is an interest in exercise alternatives that may be performed not only at home, but also in open spaces.…”
Section: What Does This Article Add?mentioning
confidence: 99%
“…As a timely example amidst the COVID-19 pandemic (Pinto et al, 2020), SIT-WB requires no additional equipment and can be easily performed alone indoors or outdoors. Give that another rising ACSM fitness trend (thirteenth position) is outdoor activities, it appears that there is an interest in exercise alternatives that may be performed not only at home, but also in open spaces.…”
Section: What Does This Article Add?mentioning
confidence: 99%
“…Previous studies investigated the impact of COVID-19 on physical activity in different age clusters and in different regions [ 19 , 20 , 21 ]. Reports have indicated that the COVID-19 pandemic-related public health restrictions appear to have led to reductions in physical activity [ 22 , 23 , 24 , 25 ]. We hypothesized that the extended periods of lockdown in Bangladesh may have adversely impacted physical activity and increased sedentary behaviors in the population.…”
Section: Introductionmentioning
confidence: 99%
“…These inconveniences were mainly related to the negative influence of cognitive, behavioral, and physical symptoms of mask-wearing daily and during leisure activities [ 9 , 10 ]. As such, the amount of physical activity has declined due to self-isolation and social distancing due to the COVID-19 outbreak, and the discomfort of mask-wearing influences physical activity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%